Gifted and Talented Curriculum and Services at Islamic Elementary Schools - Latifah, Latifah; Syafril, Syafrimen; Amriyah, Chairul (Postgraduate Program Magister Pendidikan Agama Islam, 2024)
Curriculum and services for gifted and talented students are extremely important. This study employed the SLR (Systematic Literature Review) method, which involves carefully determining, identifying, and evaluating significant research on a specific phenomenon or topic. Based on the predetermined theme, the researchers acquired the data from research journal articles indexed by Scopus and accredited by Sinta 1 and 2. The data was analyzed using the Nvivo 12 Plus program. The results of this study cover curriculum and services for gifted and talented students at Madrasah Ibtidaiyah (Islamic elementary schools), such as differentiated curriculum, challenging curriculum, responsive curriculum, the curriculum of differentiated pedagogy, and acceleration. The services comprise academic services, school counseling, teachers' role in gifted and talented education services, inclusive education services, and the function of school psychologist in ensuring that all students in Indonesia have equal chances to reach their full potential. Suppose curriculum and services for gifted and talented students align with student needs. In that case, the education program for gifted and talented students will be carried out appropriately so that they can channel their talents and abilities to the fullest extent.